Neonatal Hypoxia Ischaemia: Mechanisms, Models, and Therapeutic Challenges - Millar, Lancelot J.; Shi, Lei; Hoerder-Suabedissen, Anna; Molnár, Zoltán (Frontiers in Cellular Neuroscience, 2017)
Neonatal hypoxia-ischaemia is the most common cause of death and disability in human neonates, and is often associated with persistent motor, sensory, and cognitive impairment. Improved intensive care technology has increased survival without preventing neurological disorder, increasing morbidity throughout the adult population. Early preventative or neuroprotective interventions have the potential to rescue brain development in neonates, yet only one therapeutic intervention is currently licensed for use in developed countries. Recent investigations of the transient cortical layer known as subplate, especially regarding subplate's secretory role, opens up a novel set of potential molecular modulators of neonatal hypoxiaischaemia injury. This review examines the biological mechanisms of human neonatal hypoxia-ischaemia, discusses evidence for the relevance of subplate-secreted molecules to this condition, and evaluates available animal models. Neuroserpin, a neuronally-released neuroprotective factor, is discussed as a case study for developing new potential pharmacological interventions for use post-ischaemic injury.